Biosintesis Nanopartikel Hidroksiapatit Termodifikasi Ekstrak Daun Gedi (Abelmoschus manihot L) sebagai Agen Antibakteri - Hariyanto, Yuanita Amalia; Jayanti, Meilani; Asari (BRILIANT: Jurnal Riset dan Konseptual, 2025)
A tuna bones, particularly in the jaw region, constitute a category of food waste prevalent in North Sulawesi. Hydroxyapatite can be produced from tuna jaws. Abelmoschus manihot L (gedi) can improve the efficacy of hydroxyapatite as an antibacterial agent owing to its bioactive components. This study aimed to assess the antibacterial efficacy of hydroxyapatite treated with Abelmoschus manihot L extract. The samples were produced through multiple stages: preparation of tuna fish bones, synthesis of hydroxyapatite nanoparticles (nHA), extraction of gedi leaves and biosynthesis of nHA from gedi leaf extract. Biosynthesis was conducted via the co-precipitation technique with diverse compositions. The samples were then analyzed using FTIR and TEM, and their antibacterial activity was assessed using the well diffusion method. According to the results of the FTIR study, functional groups from the gedi leaf extract were detected at wave numbers 1731 cm-1, 1234 cm-1, and 896 cm-1, and nHA was discovered at wave numbers 576 cm-1, 608 cm-1, 964 cm-1, and 1041 cm-1, indicating the phosphate group. Furthermore, the results of the TEM investigation revealed that the samples formed spheres smaller than 100 nm. The antibacterial activity of gedi extract/nHA at concentrations of 0.5%, 1%, and 1.5% revealed the presence of inhibitory zones in the strong and very strong categories for S. aureus bacteria. Meanwhile, E. coli bacteria's inhibitory zones were moderate to strong. This suggests that gedi/nHA extract possesses antibacterial properties, making it ideal for use in biomedical applications.